Two dimensional echocardiographic categorisation of the univentricular heart. Ventricular morphology, type, and mode of atrioventricular connection. - Rigby, M L (1981)
Most univentricular hearts have two chambers in their ventricular mass, only one of which possesses an atrioventricular connection. Categorisation into univentricular heart of right, left, or indeterminate type, using two dimensional echocardiography has been successfully achieved in 122 out of 132 patients to whom this technique has been applied. Thus, right ventricular rudimentary chambers in 84 univentricular hearts of left ventricular type were shown to be anterosuperior and either to the right or left. In contrast, left ventricular rudimentary chambers in 25 univentricular hearts of right ventricular type were posteroinferior and to the right, left, or directly posterior. Thirteen univentricular hearts of indeterminate morphology were characterised by absence of rudimentary chamber on angiography and echocardiography. The trabecular pattern of both main and rudimentary chambers were separately identified in some of the patients with univentricular hearts of right and left ventricular type and two dimensional echocardiography also illustrated the mode of atrioventricular connection, either via two atrioventricular valves, a common valve, or a valve straddling or overriding the trabecular septum. Finally it was also possible to distinguish absent atrioventricular connection from an imperforate valve in 10 patients.